Inspection Resistant Memory: Architectural Support for Security from Physical Examination - Valamehr, Jonathan; Chase, Melissa; Kamara, Seny; Putnam, Andrew; Shumow, Dan; Vaikuntanathan, Vinod; Sherwood, Timothy and (Proceedings of ISCA 2012., 2012)
The ability to safely keep a secret in memory is central to the vast majority of security schemes, but storing and erasing these secrets is a difficult problem in the face of an attacker who can obtain unrestricted physical access to the underlying hardware. Depending on the memory technology, the very act of storing a 1 instead of a 0 can have physical side effects measurable even after the power has been cut. These effects cannot be hidden easily, and if the secret stored on chip is of sufficient value, an attacker may go to extraordinary means to learn even a few bits of that information. Solving this problem requires a new class of architectures that measurably increase the difficulty of physical analysis. In this paper we take a first step towards this goal by focusing on one of the backbones of any hardware system: on-chip memory. We examine the relationship between security, area, and efficiency in these architectures, and quantitatively examine the resulting systems through cryptographic analysis and microarchitectural impact. In the end, we are able to find an efficient scheme in which, even if an adversary is able to inspect the value of a stored bit with a probabilistic error of only 5%, our system will be able to prevent that adversary from learning any information about the original un-coded bits with 99.9999999999% probability.